Effects of Legume, Molasses and Urea Inclusion on the Quality of Dwarf Napier and King Grass Silages - Selaman, Masturi (2004)
Silages were prepared from tropical grasses; king grass (Pennisetum purpureum x P.typhoides) and dwarf napier (Pennisetum purpureum) either alone or with the addition of gliricidia (Gliricidia sepium) and leucaena (Leucaena leucocephala).Other treatments include the addition of urea (3%) and urea and molasses (3 and 10%,respectively). The experiment was conducted to evaluate the effects of shrub legumes on the silage quality of tropical grasses and to compare them with the effects of additives such as urea and urea-molasses.The results showed that the inclusion of both legumes increased dry matter percentage(from 15.7% to 20.7%) and crude protein (from 6.2% to 9.0%) contents of both silages. On the other hand, legume inclusion resulted in reduction of Neutral Detergent Fiber (from 69.1% to 61.6%), Acid Detergent Fiber (from 44.4% to 38.6%) and Acid Detergent Lignin contents (from 15.9% to 15.5%). The inclusion of urea decreased the dry matter percentage (from 15.7% to 15.3%) and increased the pH level (from 4.9 to 5.5) of both silages. In the meantime, the inclusion of urea-molasses increased the dry matter percentage (from 15.7% to 20.7%) of both silages. Silage made from dwarf napier with the inclusion of legumes had lower NDF and ADF content and higher dry matter percentage and crude protein content than that of king grass of similar treatment. Despite improvement in quality with legume inclusion on most of the silage characteristics (low NDF, ADF, ADL and high dry matter, crude protein), lactic acid content did not increase. The inclusion of urea and urea-molasses also did not increase the lactic acid content. The experiment also showed that there were no significant effects between treatments in buffering capacity. However, between both legumes, the buffering capacity of silage with leucaena was significantly (P<0.05) higher than silage with gliricidia.In situ digestibility studies indicated that the potential degradability of king grass with the inclusion of legumes (gliricidia and leucaena) was higher (69.6% and 66.2%, respectively) when compared with solely grass (59.5%). The inclusion of both legumes to dwarf napier also increased (74.8% and 71.1% for gliricidia and leucaena,respectively) the potential degradability. In conclusion, legume inclusion to king grass and dwarf napier improved nutritive value of the silages